Sexual and reproductive health needs of Venezuelan women migrants - Gutiérrez Ramos, Miguel (2023)
Objective: To determine the sexual and reproductive health needs of the Venezuelanmigrant population residing in Lima and Trujillo. Methods: The sample consistedof 1,616 women, including 1,114 women from the southern cone of Lima and 502women from the province of Trujillo. A survey was applied to evaluate the followingdimensions: population characteristics, health service requirements, maternal health,family planning, cervical and breast cancer prevention, and sexually transmittedinfections. Results: Most of the Venezuelan women were between 20-34 yearsold. They had an identity card in 66.8%; however, 60% of them did not have a validdocument and more than 80% did not have their migratory status regularized. 46%were cohabiters and 40.8% were single. 56.7% reported having secondary education.82.2% had a monthly family income of less than 900 soles; 75.1% in Lima and 94% inTrujillo reported not having any type of insurance. Only 48% used any contraceptivemethod, preferably long-acting reversible contraceptive methods. Between 78%-85.1% did not use cervical cancer prevention services and more than 90% did notuse breast cancer prevention services. Sexually transmitted infections were presentin 2 and 5% of the surveyed population. Conclusion: The sexual and reproductivehealth (SRH) profile of the Venezuelan migrant population in the study areas had itsown characteristics that was not comparable with the vulnerability of the Peruvianpopulation, and reveals that they have SRH needs that require attention.